Tra economia e politica: l'internazionalizzazione di Finmeccanica, Eni ed Enel - RENDA, Francesco (Studi e saggi, 2010)
In an economic system dominated by small and medium enterprises, striking among the large companies are Finmeccanica, Eni and Enel, partially controlled by the Ministry of the Economy and Finance. What are the links between politics and the choices of these companies? Have the changes in the political colour of the governments modified the entrepreneurial policies? Starting from the partial privatisation of these large companies, the book seeks to trace the thread linking politics and economics.